2007
DOI: 10.1186/1471-2407-7-123
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the cytochrome P450 genes CYP1A2, CYP1B1, CYP3A4, CYP3A5, CYP11A1, CYP17A1, CYP19A1and colorectal cancer risk

Abstract: Background Cytochrome P450 (CYP) enzymes have the potential to affect colorectal cancer (CRC) risk by determining the genotoxic impact of exogenous carcinogens and levels of sex hormones. Methods To investigate if common variants of CYP1A2, CYP1B1, CYP3A4, CYP3A5, CYP11A1, CYP17A1 and CYP19A1 influence CRC risk we genotyped 2,575 CRC cases and 2,707 controls for 20 single nucleotide polymorphisms (SNPs) that have not previously been shown to have functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 21 publications
7
33
2
1
Order By: Relevance
“…In order to further understand our results, we performed literature searches for the top 10 up and downregulated genes using the Gene Cards and PubMed databases. Of these 20 genes, 16 had a known association with HCC (Reubi et al, 2000;Okabe et al, 2001;Kim et al, 2004;Chen et al, 2006) or other tumors (Hein, 2002;Tomonaga et al, 2003;Agundez, 2004;Lu et al, 2005;Osthus et al, 2005;Hayward and Fry, 2006;Bethke et al, 2007). Therefore, our results are consistent with the literature.…”
Section: Discussionsupporting
confidence: 83%
“…In order to further understand our results, we performed literature searches for the top 10 up and downregulated genes using the Gene Cards and PubMed databases. Of these 20 genes, 16 had a known association with HCC (Reubi et al, 2000;Okabe et al, 2001;Kim et al, 2004;Chen et al, 2006) or other tumors (Hein, 2002;Tomonaga et al, 2003;Agundez, 2004;Lu et al, 2005;Osthus et al, 2005;Hayward and Fry, 2006;Bethke et al, 2007). Therefore, our results are consistent with the literature.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, for Africans the most frequent genotype is CYP1B1*3*3, 68% in African Americans with the level of 87% in the Yoruba in Ibadan, Nigeria, YRI (HapMap) (20,21). The Tatar ethnic group is significantly different in distribution from genotype frequencies of Caucasians living in England, but is similar to Caucasians in general (20,22). Generally, Russians appear to differ significantly in allele frequencies of CYP1B1 from Caucasians.…”
Section: Discussionmentioning
confidence: 78%
“…It is known that the patterns of the CYP1B1 polymorphic marker (rs1056836, 4326C> G, L432V) genotype frequencies distribution has significant racial differences (20)(21)(22). For Asian populations (Chinese, Japanese, Mexicans) it is very typical to observe the predominance of CYP1B1*1*1 genotype, which varies from 67 to 91% (20).…”
Section: Discussionmentioning
confidence: 99%
“…The present study findings showed a strong LD between the three common SNPs in the CYP1B1 gene in the population. Similarly, Bethke et al (29) observed a strong LD between the five common SNPs in the CYP1B1 gene in UK.…”
Section: Discussionmentioning
confidence: 99%